Student Engagement in Online Language Learning: A Study at Universiti Tun Hussein Onn Malaysia - Abdul Kadir, Zulida (Journal of Social Transformation and Regional Development, 2023)
At times of the pandemic, online learning is vital to the learning process. It is drastically incorporated into the learning process by Malaysian students. It is also interesting to study the impact of this online learning, especially at tertiary level. A number of factors have been identified as success factors for the adoption of online learning. These factors include student perceptions and student engagement in learning. This pilot study was carried out with 33 students from various courses. A questionnaire was distributed to respondents to collect data on their perception and engagement in learning English in online courses. The results showed that they perceived English online courses very positively and were also very engaged in the lessons. It is recommended to implement blended learning to get the best results and satisfaction in the learning process.